Physiological and sanitary quality of black bean seeds dependent on storage time and initial seed moisture content - Menegaes, Janine Farias; Nunes, Ubirajara Russi; Fiorin, Tatiana Tasquetto; Swarowsky, Alexandre; Munareto, Janete Denardi (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Black beans (Phaseolus vulgaris L.) are a species of great importance for family farming, both for food security and socioeconomic activity. The objective of this work was to assess the physiological and sanitary viability of black bean seeds stored with different initial moisture contents and cold storage periods. It was used a completely randomized design, 3×5 (seed moisture levels: 10, 13 and 16%, and storage periods: 0, 3, 6, 9 and 12 months in cold rooms, with four repetitions). Black bean seeds belonging to variety IPR88 Uirapuru were grown in the municipality of Santa Maria, Brazil, harvested in March 2020, and stored in a cold room (15ºC and 40% RH) in Kraft paper bags (brown type, 1.0 kg). Physiological variables and sanitary quality were assessed through laboratory tests. According to the results, it was possible to verify that the physiological and sanitary quality of black beans were negatively affected with the increase of storage period, in all grades. However, it is possible to store these seeds with moisture contents of 10 or 13% for a period of up to nine months in a cold room, with a 70% germination quality.